Komuniti fauna ikan di Sungai Kesit, Batang Lemanak, Engkilili, Sarawak - Juillif, bin Sipin. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study was conducted to determine the diversity offish fauna community in Sungai Kesit, Batang Lemanak, Engkilili, Sarawak. During the study period, the water was generally clear, fast flowing with rocky and sandy substrate at the bottom ofthe river. Four fishing methods used were gill net, cast net, electroshocker and hook and line. Thirty-seven species belonging to 10 families and 24 genera were recordedfrom the sampling sites. From the 793 individuals caught, the two dominantfamilies are Cyprinidae and Balitoridae representing 55% and 34% ofthe number ofindividual caught respectively. The commonly caught individuals were from the genera Gastromyzon (29.8%), Rasbora (21.3%) and Puntius (20.9%). Among the six Gastromyzon species, Gastromyzon contractus is the dominant individuals caught (67 individuals). Among the 37 species caught from the study area, Puntius lateristriga is the dominant species (J 40 individuals). This study showed that the number ofspecies present in Sungai Kesit is more than those reported for Batang Lemanak. This is because Batang Lemanak watersheds have been logged and the water quality has deteriorated. This is reflected in the high amount oftotal suspended solids in the water. In contrast, Sungai Kesit watershed has not been logged and the condition is still pristine.